A abordagem transversal na formação crítica, reflexiva e humanista de alunos de um curso de Letras: Inglês - Silva, João Batista Teixeira da (2006)
This research focuses on the adoption of Transversality in the critical formation of students in an English teacher formation course. Our objective is to show that this approach gives the students the opportunity of building knowledge in interaction with reality. Facing themes of social relevance, the pre-service teacher develops communicative and linguistic abilities through reports and discussions, which will enable him / her to develop critical thinking. This criticism gives the student the possibility of experiencing linguistic characteristics of argumentative discourse. This study is supported by theories which include: a. Transversality, as seen by Celani, Yus and others; b. the teaching-learning interaction according to Vygostky s Zone of Proximal Development; c. ethics; and d. inclusive education. Data is analyzed according to qualitative methodology and data collection followed ethnographic procedures. The participants are the students and teacher in an English teacher formation course at the Pontifícia Universidade Católica de São Paulo. Data was obtained from presentations delivered at the end of a thematic discussion adopting a transdisciplinary approach. An audio recording and subsequent transcription were performed. The results suggest that the students frequently adopted an argumentative discourse to express themselves critically, moving beyond the narrative discourse borders proposed in the original course programme. It is our belief that a critical, committed formation of English pre-service teachers will foster the relevance of their role as educators of critical and inclusive citizens. This is the motivation for this study to be carried out and presented